PENGENDALIAN VEKTOR DBD DENGAN TANAMAN ANTI NYAMUK - Tatontos, Erlin Yustin; Urip, Urip; Kristinawati, Erna (Jurnal Pengabdian Masyarakat Sasambo, 2024)
In Indonesia, Dengue Hemorrhagic Fever (DHF) fluctuates every year and tends to increase in morbidity rates and the distribution of affected areas. Extraordinary Events (KLB) DHF occurs almost every year in different places and its occurrence is difficult to predict. Report on the results of the 2021 Community Health Center work program, Larval Free Rate (ABJ) in the Babakan Community Health Center work area in 2021 94.4%. ABJ in Babakan Village is 94% and ABJ in Cakranegara Selatan Baru Village is 87%. Control of the dengue mosquito vector is by using chemical insecticides at home such as mosquito coils, sprays, lotions and other forms. Many of these anti-mosquito drugs have a risk of harm to humans and the environment due to the use of toxic products contained in anti-mosquito drugs. The aim of Community Service (PKM) is to determine the empowerment of Health Cadres at Posyandu Prima in controlling dengue vectors by using anti-mosquito plants in the Babakan Community Health Center working area. The solution offered in PKM is the empowerment of health cadres at Posyandu Prima through promotional efforts regarding Dengue Hemorrhagic Fever and its eradication as well as Preventive efforts through controlling dengue vectors by using anti-mosquito plants to increase ABJ. The results that have been achieved after providing outreach to health cadres and village officials as partners are increased knowledge and understanding about dengue fever and vector control. Health cadres' skills in larva surveying and the use of anti-mosquito plants after training increased. The evaluation results of calculating the ABJ value in Babakan Village and Cakranegara Selatan Baru Village increased to ≥ 95% according to WHO standards.